Material evaluation: 'Fun With English' module / Tengku Intan Suzila Tengku Sharif, Harlina Yunus @ Junor and Mohd Yusri Mohd Noor - Tengku Sharif, Tengku Intan Suzila; Yunus @ Junor, Harlina; Mohd Noor, Mohd Yusri (2006)
Any module deemed necessary has to undergo a process of evaluation. The purpose of material evaluation is to reveal the strength and weakness of materials used, thus, offering vital information for improvement purposes. Therefore. the 'Fun With English' module is deemed fit for an evaluation as it has been carried out in three English motivation camps which were conducted as community service programmes by lecturers of the Academy of Language Studies. UiTM Pahang. It is hoped that this evaluation will shed some light on the success of the programmes as well as to identify the strength and weaknesses of the module itself. A framework of learner questionnaire (Ellis 1998:235) was adapted to serve this research. A number of 63 school children, who had the opportunity to experience the running of the module in the previous community service programme, were the respondents of the questionnaire. The questionnaire was distributed after the completion of each activity. The answers given by the schoolchildren acted as data which offered essential output, suitable for a comprehensive analysis and understanding. The results are hoped to suggest language learning elements that need enhancement in order for UiTM to serve the community better.